As equações diofantinas lineares e o livro didático de matemática para o ensino médio - Oliveira, Silvio Barbosa de (2006)
This work involves a qualitative study of how the theme of linear Diophantine equations is approached in mathematics textbooks for high school students. Using the methods associated with content analysis (Bardin, 1977), I search for references, in both explicit and implicit forms, to these equations in two different sets of high school mathematics textbooks, both of which had been approved in the last PNLEM (a national project for the assessment of high school textbooks). Although elementary number theory has been highlighted by researchers in mathematics education, such as Campbell and Zazkis (2002), as a subject apt for the introduction and development of fundamental mathematical ideas in compulsory education, the results of this investigation indicate that it receives little attention in the textbooks analysed